Fisheries, a source of livelihood in Marngar Village Cluster, Ri-Bhoi District of Meghalaya - Singh, S Gojendro; Devi, N Peetambari; Singh, H Jiten; Sinha, P K; Das, S K; Laha, R; Singha, A K; Chahal, V P (Indian Farming, 2019)
Fish and fisheries products have played a major role in food security in the economy of the Northeast region in India. The district Ri-Bhoi in Meghalaya being a semi-hilly region has great potential for fisheries and aquaculture. However, majority of the farmers have little or no knowledge about the scientific fish culture. Therefore, a maiden attempt has been made through the Farmer First Programme of ICAR-Research Complex for NEH Region, Umaim to sensitize and motivate the farmers of Marngar village about the scope and profitability of fish farming venture by demonstrating different technologies recommended by the ICAR-Research Complex for NEH Region, Umiam for improving the livelihood and socio-economic condition of the local farmers through fish farming.